Facile solution combustion synthesized, Li doped ZnO nanostructures for removal of abiotic contaminants. (October 2021) - Yadav, Suprabha; Jindal, Jitender; Mittal, Anuj; Sharma, Shankar; Kumari, Kavitha; Kumar, Naveen
Abstract: ZnO is a versatile photocatalytic material, yet it needed further modifications to explore it on the commercial scale. In the present study, photoactive Li doped ZnO nano-materials with different Li content were synthesized by adopting a facile low-temperature solution combustion approach. Li was introduced to improve ZnO characteristics correspond to photocatalytic efficiency. The effect of lithium doping on morphology, crystallinity, chemical state, and optical properties were investigated by utilizing various advanced techniques. The characterization analysis confirms the presence of thermally stable, well-crystalline wurtzite ZnO with a low bandgap and porous nature. Organic dye, Cibacron Red (CR), and a pesticide, Triclopyr (TC) were taken as model pollutants to evaluate the photodegradation performance of all samples under UV light source. Li doped ZnO nanomaterials containing 5 mol% Li attained the highest photocatalytic activity for the removal of both pollutants. The results of the study demonstrate that a strong electronic interaction between Li and ZnO results in the improvement of charge transferability and retards their recombination. The alteration in optical and surface properties of ZnO due to the substitution of Li into ZnO lattice was another reason for the superior activity of Li doped ZnO. Highlights: Energy efficient solution combustion approach applied in synthesis. Low power light source used for the degradation process. 5 mol% Li contain ZnO showed best photocatalytic activity. Oxygen vacancies leads to high activity of the Li doped ZnO samples.